A comprehensive review and comparison of L-tryptophan biosynthesis in Saccharomyces cerevisiae and Escherichia coli - Ren, Xinru; Wei, Yue; Zhao, Honglu; Shao, Juanjuan; Zeng, Fanli; Wang, Zhen; Li, Li (Frontiers in Bioengineering and Biotechnology, 2023)
L-tryptophan and its derivatives are widely used in the chemical, pharmaceutical, food, and feed industries. Microbial fermentation is the most commonly used method to produce L-tryptophan, which calls for an effective cell factory. The mechanism of L-tryptophan biosynthesis in Escherichia coli, the widely used producer of L-tryptophan, is well understood. Saccharomyces cerevisiae also plays a significant role in the industrial production of biochemicals. Because of its robustness and safety, S. cerevisiae is favored for producing pharmaceuticals and food-grade biochemicals. However, the biosynthesis of L-tryptophan in S. cerevisiae has been rarely summarized.The synthetic pathways and engineering strategies of L-tryptophan in E. coli and S. cerevisiae have been reviewed and compared in this review.Furthermore, the information presented in this review pertains to the existing understanding of how L-tryptophan affects S. cerevisiae's stress fitness, which could aid in developing a novel plan to produce more resilient industrial yeast and E. coli cell factories.